ANALISIS KONFLIK SOSIAL MASYARAKAT TERHADAP PERUBAHAN ARAH KIBLAT YANG TERJADI DI KELURAHAN TONRORITA KECAMATAN BIRINGBULU KABUPATEN GOWA - Nurdin, Nurdin; HL, Rahmatiah (Universitas Islam Negeri Alauddin Makassar, 2026)
Abstract Changes in the qibla direction based on the results of scientific measurements often lead to differences in perspectives and social conflicts within the community, particularly when they are not accompanied by adequate communication and socialization. This study aims to analyze the community's responses, the factors contributing to social conflict, and the roles of local government, religious leaders, and mosque administrators in resolving conflicts arising from changes in the qibla direction in Tonrorita Village, Biringbulu District, Gowa Regency. This study employed a qualitative method with a normative-sharia approach. Data were collected through observation, in-depth interviews, and documentation, and were subsequently analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the community's responses to the change in qibla direction in Tonrorita Village were divided into three groups: those who opposed, supported, and remained neutral. The opposing group maintained the previous qibla direction because it was considered a legacy of earlier religious scholars and expressed concerns that the change would incur costs and reduce worshippers' comfort. The supporting group viewed the adjustment based on scientific measurements as an effort to improve the quality of worship, which could be implemented by adjusting the prayer row positions without altering the mosque building. Meanwhile, the neutral group chose to follow the majority decision in order to maintain harmony and social relations within the community. The conflict was triggered by the results of the qibla direction measurement conducted by the Ministry of Religious Affairs, insufficient socialization, differences in understanding between traditional and scientific approaches, and the reluctance of some community members to accept differing opinions. Efforts by the local government, religious leaders, and mosque administrators through deliberations have not yet resulted in an agreement accepted by all parties. Therefore, conflict resolution requires open communication, effective socialization, persuasive approaches, and the involvement of the entire community to foster mutual understanding and harmony. The implication of this study is that changes in the qibla direction require a participatory, communicative, and persuasive approach. Therefore, coordination, education, and continuous socialization need to be strengthened to minimize conflict and maintain social harmony within the community. Keywords: Analysis, Social Context, Qibla Direction Change